An application of an extended effort-reward imbalance model to police absenteeism behaviour. Issue 4 (6th June 2016) - Allisey, Amanda; Rodwell, John; Noblet, Andrew
Abstract : Purpose: – Frequent absences from work can be highly disruptive, whilst also potentially indicating problematic working conditions that can lead to increased withdrawal behaviour. The purpose of this paper is to test the predictive capability of an expanded effort-reward imbalance model on employee absenteeism within the context of policing. Design/methodology/approach: – Three separate reward systems are identified by the effort-reward imbalance model. In this study, the authors assessed these individual components for their contribution to officer withdrawal behaviour in the form of absenteeism frequency. Data were gathered from a sample of operational officers ( n =553) within a large Australian police agency. Findings: – Findings indicate that there was a strong influence of social rewards such as social support and recognition in the workplace on officer absenteeism rates. Low workload was associated with a higher frequency of absenteeism suggesting a potential underloading effect. There were a number of significant interactions providing support for the effort-reward imbalance mechanism and the separation of the reward construct. Security rewards were particularly influential and significantly moderated the relationship between effort and absenteeism. Research limitations/implications: – Differential effects of occupational rewards were identified in the study, indicating that there are significant opportunities for expansion of the effort-reward imbalance model along with opportunities for HRM practitioners in terms of employee recognition and remuneration programmes. This research was focused on a specific sample of operational officers, therefore should be expanded to include multiple occupational groups. Originality/value: – This paper considers and expanded model of worker strain and contributes a longitudinal assessment of the association between perceived effort and reward systems and worker absenteeism.